2022
DOI: 10.1371/journal.pone.0271138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antidiabetic agents on Alzheimer’s disease biomarkers in experimentally induced hyperglycemic rat model by streptozocin

Abstract: Background Alzheimer’s disease is the most common cause of dementia in the elderly population. It is characterized by the accumulation of amyloid β and intraneuronal neurofibrillary tangles in the brain. Increasing evidence shows that the disturbance of insulin signalling in the brain may contribute to the pathophysiology of Alzheimer’s disease. In type 1 diabetes, these disruptions are caused by hypoinsulinemia, but in type 2 diabetes, they are caused by insulin resistance and decreased insulin secretion. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Peptides were subjected to LC-MS/MS (liquid chromatography with tandem mass spectrometry) analysis with an UltiMate 3000 (Thermo Fisher ® , San José, CA, USA) ultrahigh-performance liquid chromatography (UHPLC) system coupled with an Orbitrap FusionTM LumosTM mass spectrometer (Thermo, San José), as follows: The peptide mixtures were loaded into a column (75 mm i.d., 30 cm long) packed in-house with a 3µm ReproSil-Pur C18-AQ resin (Dr. Maisch) with a flow of 250 nL/min. Subsequently, they were eluted with a flow of 250 nL/min, from 5% to 40% ACN, in 0.1% formic acid in a 140 min gradient (23). The mass spectrometer was set in data-dependent acquisition (DDA) mode to automatically switch between full-scan (MS) and MS/MS (MS2) acquisition.…”
Section: Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Peptides were subjected to LC-MS/MS (liquid chromatography with tandem mass spectrometry) analysis with an UltiMate 3000 (Thermo Fisher ® , San José, CA, USA) ultrahigh-performance liquid chromatography (UHPLC) system coupled with an Orbitrap FusionTM LumosTM mass spectrometer (Thermo, San José), as follows: The peptide mixtures were loaded into a column (75 mm i.d., 30 cm long) packed in-house with a 3µm ReproSil-Pur C18-AQ resin (Dr. Maisch) with a flow of 250 nL/min. Subsequently, they were eluted with a flow of 250 nL/min, from 5% to 40% ACN, in 0.1% formic acid in a 140 min gradient (23). The mass spectrometer was set in data-dependent acquisition (DDA) mode to automatically switch between full-scan (MS) and MS/MS (MS2) acquisition.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…Most studies using the ICV-STZ model are focused on the description of the behavioral [ 20 ] and morphological [ 21 ] aspects of the disease. The molecular factors of the ICV-STZ model are often assessed through techniques that target only a few genes, such as qRT-PCR [ 22 ] and Western blot [ 23 ]. Mass spectrometry (MS)-based proteomics is a powerful analytical tool commonly used to study the proteome profile of LOAD’s brain [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…While certain studies have demonstrated favorable results, contrasting outcomes marked by the absence of noteworthy effects or conflicting findings have also been reported. These inconsistencies could potentially be elucidated by disparities in multiple factors, including study architecture, specific patient demographics, variations in drug protocols, and the diverse array of metrics employed to gauge outcomes [56][57][58][59][60][61][62].…”
Section: Clinical Studies Investigating the Use Of Antidiabetic Agent...mentioning
confidence: 99%
“…Gasparini et al have demonstrated that disruptions in brain insulin signaling may play a contributory role in the pathophysiology of AD [106]. Clinical studies have revealed that AD patients exhibit reduced insulin levels and expression of the insulin receptor in the brain, as well as insulin resistance [107], all of which can trigger Aβ accumulation, tau phosphorylation, neurodegeneration and cerebral glucose metabolism impairment, and cognitive decline [108]. Hence, the perturbations in the insulin signaling pathway are increasingly recognized as a shared characteristic of both AD and diabetes, often referred to as "type 3 diabetes" [109].…”
Section: Other Pathogenic Hypothesesmentioning
confidence: 99%